Epithelioid Hemangioendothelioma in the Area of the Neurovascular Bundle of the Upper Arm Mimicking a Schwannoma of the Ulnar Nerve - Scheller, Christian; Rampp, Stefan; Prell, Julian; Strauss, Christian; John, Endres; Jörg, Ukkat; Diessel, Linda; Brandt, Silvio; Müller, Tobias (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Epithelioid hemangioendothelioma (EH) is a rare vascular malignant sarcoma. To date, there are only two published case reports of EH mimicking nerve sheath tumors of a peripheral nerve. A 41-year-old woman presented with a painful node on the inside of the upper arm and motor deficits of the ulnar nerve. Magnetic resonance imaging (MRI) follow-up and neurosonography revealed a slowly progressive, contrast-enhancing tumor in the area of the neurovascular bundle. A schwannoma of the ulnar nerve was suspected. At surgery, the tumor was adherent to the brachial artery, but not to nerves. Pathology revealed an EH. EH may mimic a nerve sheath tumor and should be taken into consideration, especially because of its potential for metastasis and fatal progression.
Keywords: epithelioid hemangioendothelioma; peripheral nerve; vascular neoplasm